Growth and yield of clusterbean (Cyamopsis tetragonoloba) grown on light-textured soils with foliar application of fermented panchgavya - KUMAWAT, R N; MAHAJAN, S S; MERTIA, R S (The Indian Journal of Agricultural Sciences, 2011)
A field study was carried out in rainy (kharif ) season of 2006 and 2007 to examine the effect of foliar application of panchgavya plus leaf extracts of neem (Azadirachta indica A, Juss.), datura (Datura metel L.) and tumba (Citrullus colocynthis L.) in 1:1 ratio on dry matter accumulation, nutrient uptake, yield and yield attributes of clusterbean (Cyamopsis tetragonoloba L. Taub.) grown on light-textured soils under irrigated conditions. The results showed that the foliar application of neem plus panchgavya increased dry matter accumulation, nutrient uptake, yield and yield attributes significantly compared to control and sole application of panchgavya. Application of neem plus panchgavya recorded higher grain (34%), straw (21%) and biological yield (25%) compared to control. Application of the sources both at branching plus flowering recorded significantly higher dry matter as well as nutrient uptake, yield and yield attributes over the application either at branching or flowering. The grain, straw and biological yields recorded 26, 22 and 23% increase, respectively with dual application of sources both at branching and flowering compared to spray at flowering only.